"The internet is not pleased": twitter and the 2017 Equifax data breach. Issue 3 (3rd July 2019) - Novak, Alison N.; Vilceanu, M. Olguta
ABSTRACT: The 2017 Equifax data breach left 144.5 million users digitally vulnerable to identity theft and future hacks. The organization's failure to provide ongoing communication and information regarding the attack, motivated users to form crisis communities within the Twitter platform. This study examines the discourses present within the platform as users discussed the data breach. Digital crisis communities provide researchers opportunities to study how public users respond and react to a digital threat, particularly one that impacts online security and privacy. Through a qualitative analysis of tweets from the 3 weeks after the breach was announced, three discourses emerged that represented user frustrations and reactions to the security violation. These include breaking news, anger and outrage, and blame attribution. The findings of this study are relevant for those studying crisis communication, the Twitter platform, and online communities.